Dependence of surface tension of fruit puree on temperature exposure - L K. Patsyuk; T. V. Fedosenko; V. V. Kondratenko; M. V. Lukyanenko (Аграрная наука Евро-Северо-Востока)
When developing food products with new properties using innovative technologies, it is important to obtain data on the physicochemical, thermal-physical and structural-mechanical properties of the processed food media. So, one of the key components in the selection of the mode of collapsing ultrasonic cavitation is the surface tension of vegetable purees. The paper presents research data (2020) on the effect of temperature on the surface tension coefficient of fruit puree of different viscosity. The objects of research are cherry plum, pear and apple puree, combined in a row by viscosity. The surface tension coefficient was determined by the stalagmometric method, for which the puree was preliminarily centrifuged. The measurements were carried out at temperatures of 25 and 35 °С. It was found that, under equal conditions of centrifugation of puree, the proportion of supernatant in pear puree is noticeably higher – 77.37 % to the weight of puree in comparison with cherry plum puree (67.20 %) and apple puree (52.75 %). This fact can be explained by the presence of stony cells in the former which form an incompressible sediment, which allows a greater separation of the dispersed phase (sediment) and the dispersion medium (supernatant). It was found that the coefficient of surface tension of fruit purees, despite the slight difference, decreases with increasing temperature. Analysis of the steepness of the slope of the curve characterizing the effect of temperature on the surface tension coefficient showed that temperature stabilization during technological processing is more required for pear puree.